Economic implications of different cork oak forest management systems - Pinheiro, A. C.; Ribeiro, N. A. (2008)
The agro-silvopastoral system “montado” dominates the landscape of the south-western Iberian Peninsula, occupies approximately 3.1 million hectares of woodland in Spain and 1.2 million hectares in Portugal. The forest system “montado” is mostly dominated by Mediterranean evergreen oaks such as cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia). The “montado” production system management aims the maintenance of a balanced sustainable land use to cope with the Mediterranean climate variability. One important issue in cork oak forests is the control shrub growth in order to prevent forest fire hazard, which is of high risk in Mediterranean climate. The two most common ways of controlling the shrub component is by mechanical destruction with soil disking (that implicates soil mobilization) or by shrub cutting (that is done with minimum impact on soil). The two referred techniques have different costs and different impacts on cork production and other goods and services (multifunctionality) of cork oak forests. In this paper, the two shrub control systems are compared and the results show that, although soil disking is more profitable than shrub cutting, the results are reversed, if one considers the carbon sequestration. This means that besides the great economic sustainability of cork oak dependence on the price of cork, the profitability of different shrub control methods depend also on the way society valuates other goods and services provided by cork oak forest
The following values have no corresponding Zotero field: secondary-title: International Journal of … periodical: International Journal of … electronic-resource-num: 10.1504/IJSSOC.2008.022571
Keywords: Cork oak; NPV; Sustainability; woodlands